KEABSAHAN HUKUM TRANSAKSI E – COMMERCE - Dewi Oktoviana Ustien (JSSHA ADPERTISI JOURNAL, 2021)
Trade transactions through the internet are very beneficial for many parties, so that these trade transactions are in great demand, not only for producers but also consumers. Now the Internet has become a special problem since it is used in trade or business activities known as E-Commerce transactions. It is recognized economically, the use of the internet has provided added value in accelerating the transaction process, but juridically, the problem of using the internet is very risky for the parties because its characteristics are very different from conventional business, making it difficult to reach by the applicable legal rules.This research uses a normative juridical approach . And the data used is secondary data which is then analyzed qualitatively. The results of the study indicate that transactions and the validity of agreements on e-commerce are said to be valid if they meet several conditions, namely as stated in Article 1320 of the Civil Code, namely the existence of agreements, skills, exchanged values, and a lawful object. Article 1458 explains about the agreement, which reads